Basic Subjects and their Arrangement:A Summary - Neelameghan, A. (Journal of Information and Knowledge, 1973)
The discussion on the modes of formation and arrangement of Basic Subjects, presented in the preceding papers is summarised. Guiding principles available for the arrangement of Basic Subjects are enumerated. Some problems for investigation are mentioned.